Neue Wege der Hochschulgovernance - Lüde, Rolf von (Hamburg University Press, 2010)
The end of the foundation phase of the Faculty of Economics and Social Sciences with the integration of the previously independent Hamburg University for Economics and Politics (Hochschule für Wirtschaft und Politik, HWP) and the former faculties for social science and economics of the University of Hamburg gave rise to a scientific symposium on higher education governance, with top-class performers. The symposium was aiming at a comparision of different management models, especially from other European countries, confront them and analyze them both from a management perspective and experience based on scientific and analytical points of view and to evaluate them. Particular attention was to the tension between centralization and decentralization relevant for all universities. The presentations are documented in this volume.